Accuracy of Blood Loss Assessments During Cesarean Deliveries [A144]. (May 2022) - Zermeno, Yuri; Kram, Jessica J.; Dickson, Elizabeth; Salvo, Nicole
Abstract : INTRODUCTION: Traditionally, during deliveries blood loss was estimated visually (Estimated Blood Loss; EBL). More recently, Quantitative Blood Loss (QBL) has been implemented to increase blood loss assessment accuracy. Our quality improvement study aimed to identify if QBL is superior to EBL in quantifying blood loss in comparison to Calculated Blood Loss (CBL). METHODS: We retrospectively reviewed all women with a cesarean delivery in one urban hospital between December 1, 2018, and December 1, 2019, who had EBL and QBL recorded. CBL, our gold standard for identifying postpartum hemorrhage, was calculated using maternal height, weight, pre- and post-delivery hematocrit. Hemorrhage was defined as blood loss ≥1, 000 mL. Basic descriptive and inferential statistics were conducted. RESULTS: Overall, 486 patients had EBL, QBL, and CBL values. The median values for EBL (600.0; IQR, 500.0–800.0) and QBL (547.5; IQR, 347.0–808.0), were significantly lower (both P <.001) than CBL (896.2; IQR, 512.4–1, 323.4). When compared to CBL, EBL had low sensitivity (12.0%; 95% CI, 7.7–16.3%) and high specificity (89.7%; 95% CI, 78.6–100.0%). QBL also demonstrated low sensitivity (22.6%; 95% CI, 17.0–28.1%) and high specificity (94.4%; 95% CI, 91.7–97.2%). The negative predictive value for EBL (58.2%; 95% CI, 53.7–62.7%) and QBL (60.2%; 95% CI, 55.5–64.9%) was low. The positive predictive value for EBL (89.7%; 95% CI, 78.6–100.0%) was greater than QBL (76.6%; 95% CI, 66.2–87.0%). Ultimately, only six additional hemorrhages were detected by QBL (35 versus 29 for EBL); on the other hand, CBL detected 153. CONCLUSION: Given the time and resources necessary to calculate QBL, this study questions its utilization and/or superiority to EBL in the detection of postpartum hemorrhage.